Effect of building performance on floor response spectra - Kumar, Ratnesh; Singh, Yogendra; Tripathi, Sudhanshu (Journal of Structural Engineering, 2025)
Safety of nonstructural elements including equipment and services is crucial in a building subjected to earthquake. Currently available guidelines provide design actions for acceleration sensitive components, independent of building characteristics. The aim of the present study is to estimate the amplification of motion along height due to vibrations of building structure and to study the effect of ductility demand, which is the primary indicator of building performance. A 10 storey existing building has been considered. Three different levels of earthquake ground shaking intensities resulting in three different ductility demands have been considered. The building has been subjected to sets of 10 accelerograms consistent with the design response spectra corresponding to each ground shaking level. The floor responses have been obtained using Non-linear Time History Analysis and average amplification factors on each floor have been studied. The results show that the floor response of lower stories is mainly governed by the ground shaking characteristics, but for the higher stories the effect of the dynamic characteristics of building structure increases. Further, the amplification of floor acceleration reduces with increasing non-linearity in the building and the effect is more pronounced corresponding to the first mode for the considered building.